2019
DOI: 10.1111/epi.14720
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of interictal spike propagation in children with refractory epilepsy

Abstract: Summary Objective Interictal spikes are a characteristic feature of invasive electroencephalography (EEG) recordings in children with refractory epilepsy. Spikes frequently co‐occur across multiple brain regions with discernable latencies, suggesting that spikes can propagate through distributed neural networks. The purpose of this study was to examine the long‐term reproducibility of spike propagation patterns over hours to days of interictal recording. Methods Twelve children (mean age 13.1 years) were retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…Our results suggest that ictal oscillations observed during epileptic spasms reproducibly propagate along direct corticocortical white matter pathways. This observed consistency in propagation broadly parallels other research characterizing epilepsy as a network disorder, 39 including demonstrations of reproducibility 40 and corticocortical pathway dependance 41 in spatiotemporal dynamics of interictal spikes and evoked potentials 42 . However, the timescale of our observed signal propagation, on the order of hundreds of milliseconds, is not commensurate with expectations of rapid myelinated conduction, complicating neurophysiological interpretations of our results.…”
Section: Discussionsupporting
confidence: 84%
“…Our results suggest that ictal oscillations observed during epileptic spasms reproducibly propagate along direct corticocortical white matter pathways. This observed consistency in propagation broadly parallels other research characterizing epilepsy as a network disorder, 39 including demonstrations of reproducibility 40 and corticocortical pathway dependance 41 in spatiotemporal dynamics of interictal spikes and evoked potentials 42 . However, the timescale of our observed signal propagation, on the order of hundreds of milliseconds, is not commensurate with expectations of rapid myelinated conduction, complicating neurophysiological interpretations of our results.…”
Section: Discussionsupporting
confidence: 84%
“…Previous literature suggests that the effects of anesthesia or acute effects of electrode placement are minimized 72 h post‐implantation 11 . It was demonstrated that patient‐specific interictal spike propagation patterns are consistent across multiple 30‐min segments including different stages of vigilance 10 . The 2‐h recordings were split in two 1‐h epochs.…”
Section: Methodsmentioning
confidence: 99%
“…11 It was demonstrated that patientspecific interictal spike propagation patterns are consistent across multiple 30-min segments including different stages of vigilance. 10 The 2-h recordings were split in two 1-h epochs. Analysis was run separately for each epoch.…”
Section: Seeg Recording and Segment Selectionmentioning
confidence: 99%
“…Therefore, rather than the spatial extent of the irritative zone, its intrinsic dynamic must be characterized. To date, the resection of sources of propagating spike patterns identified in invasive stereoEEG recordings are associated with good surgery outcome [ 42 , 43 ] https://www.zotero.org/google-docs/?T7WkMp . The clinical analysis of MEG interictal patterns should therefore localize spike generators at latencies preceding the spike peak, where the SNR is higher, in order to account for spatial propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rather than the spatial extent of the irritative zone, its intrinsic dynamic must be characterized. To date, the resection of sources of propagating spike patterns identified in invasive stereoEEG recordings are associated with good surgery outcome [42,43]https://www. zotero.org/google-docs/?T7WkMp.…”
Section: Discussionmentioning
confidence: 99%